PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS NEGERI (SMA N) DAN MADRASAH ALIYAH NEGERI (MA N) POKJA 1 KABUPATEN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of the Headmaster Leadership, Working Enveronment and Working Motivation toward Teachers Performance of Public Senior High School and Islamic Public Senior High School (SMA N & MA N) Teacher of Wonrk Group of 1 Sleman Regency. This research was aimed to find out the influence of headmaster leadership, working enveronment and working motivation on the performance of public Senior Hight School teachers of Work Group 1 in Sleman Regency. This research data were collected using questionaires distributed to public teacher at the following schools : SMA N 1 Kalasan, SMA N 1 Prambanan, SMA N 1 Depok and MAN Maguwoharjo. There were 166 teachers in the population. The sample of 110 teachers were selected using Random sampling. The result of the research shows that the headmater leadership, working enveronment,and working motivation have positive and significant influence on teachers performance. The headmaster leadership contrebuted effectively 7, 26 % to teachers performance. The working enveronment contributed effectively 1, 71 % to teachers performance and working motivation contributed effectively 19, 21 % to teaachers performance.